Scala for the impatient - Horstmann, Cay S., 1959- (Addison-Wesley Professional, 2022)
Scala 3--A Clear, Concise Guide Scala 3 is concise, consistent, flexible, robust, and efficient, but there's a lot to learn and navigating features and improvements can be challenging. Scala for the Impatient, Third Edition, is a complete yet concise guide that reflects the major enhancements of Scala 3, from improved syntax and revamped type system to powerful contextual abstractions. This indispensable tutorial offers a faster, easier pathway for learning today's Scala. Horstmann--author of the programming classic, Core Java--covers everything working developers need to know, focusing on hands-on solutions, not academic theory. Given the size and scope of Scala 3, there's plenty to cover but it's presented in small chunks organized for quick access and easy understanding, with plenty of practical insights and focused sample code. Get started quickly with Scala 3 interpreter, syntax, tools, and current usage Master core language features: functions, arrays, maps, tuples, packages, imports, exception handling, and more Design and build better object-oriented code with Scala 3 Use Scala for real-world programming tasks: working with files, regular expressions, and processes Work with higher-order functions and the powerful Scala collections library Create concurrent programs with Scala futures Understand the Scala type system, including revamped enums, intersection and union types, and enhanced type inference Use contextual abstractions to easily extend class hierarchies, enrich existing classes, perform automatic conversions, and elegantly hide tedious details Apply advanced "power tools" such as annotations and given values Discover how to "program with types," analyzing and generating types at compile time Get a taste of what's now possible with Scala macros If you're a Java, Python, C++, or C# programmer who's new to Scala or functional programming--or even if you've already used earlier versions of Scala--this guide will help you write code that's more robust, more efficient, and more secure. Register your book for convenient access to downloads, updates, and/or corrections as they become available. See inside book for details.